Managing the offender-to-victim transition with parental support, low neighborhood disorder, positive school culture, and moral cognition: protective and promotive factors and the person proximity effect - Walters, Glenn D. (Criminal justice studies, 2022)
Victim-offender overlap is examined from the standpoint of offending leading to victimization by way of the peer selection effect, routines activities and lifestyle choice, and person proximity. The current investigation focused on the potential role of protective and promotive factors in managing the offender-to-victim transition. Participants were 1,760 juveniles from the British-based longitudinal Offending, Crime and Justice Survey (OCJS) who were under the age of 18 at the start of the study. Three waves of data were analyzed, the preliminary results of which confirmed the person proximity effect (offending → peer delinquency → victimization). Although four potential protective/promotive factors (parental support, low neighborhood disorder, positive school culture, and moral cognition) failed to interact with the first two variables in the person proximity sequence (i.e. offending and peer delinquency), there was some evidence of a promotive effect for two of these factors. Parental support, for instance, produced a modest deterrent effect on Wave 2 peer delinquency, whereas low neighborhood disorder directly reduced the incidence of victimization. Even with these promotive effects, the person proximity effect remained intact. Further research is required to replicate the present findings and identify additional protective/promotive variables that may help mitigate the person proximity effect.